2013
DOI: 10.2514/1.b34743
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Biodiesel and Diesel Jets in Gaseous Crossflow

Abstract: This study compares the fundamental spray characteristics, such as penetration depth, droplet diameter, velocity, and volume flux of, biodiesel and diesel as well as their blends. Liquid jet is injected into an air crossflow with a speed of 58 m∕s. A series of experimental tests covering Weber numbers from 29-82, and momentum flux ratios from 10-133, are conducted using the shadowgraph method and phase Doppler particle analyzer. The shadowgraph images are processed to find the penetration depth and to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Although a definitive correlation with the liquid viscosity was not possible in their study, various effects were proposed as possible influences, including the liquid properties, atomization, and the column break mode. The influence of the breakup mode is in agreement with that in the work of Farvardin et al 15 As such, predictions of the spray characteristics when one type of fuel is directly substituted with another may not be always reliable. Consequently, the direct substitution of fuels with similar physical properties may not produce the expected spray development.…”
Section: Introductionsupporting
confidence: 79%
See 3 more Smart Citations
“…Although a definitive correlation with the liquid viscosity was not possible in their study, various effects were proposed as possible influences, including the liquid properties, atomization, and the column break mode. The influence of the breakup mode is in agreement with that in the work of Farvardin et al 15 As such, predictions of the spray characteristics when one type of fuel is directly substituted with another may not be always reliable. Consequently, the direct substitution of fuels with similar physical properties may not produce the expected spray development.…”
Section: Introductionsupporting
confidence: 79%
“…Experimentally, it has been observed that more viscous liquid jets are deflected laterally by the cross flow, more than the less viscous jets. 14,15,40 An interpretation of this observation can be based on the more developed liquid velocity radial profile in the more viscous liquid jet.…”
Section: Temporal Developmentmentioning
confidence: 99%
See 2 more Smart Citations